Biochar : A Sustainable Approach - Showkat Ahmad, Bhawani; Aamir Hussain, Bhat; Rafeah, Wahi; Zainab, Ngaini (Springer, 2024)
This book highlights the latest research on biochar, a low-cost carbonaceous material produced from biomass, and is regarded as an economical substitute to the activated carbon. The book describes the production and the characteristics of biochar through various techniques/methods such as pyrolysis, gasification, torrefaction, and hydrothermal carbonization of carbonaceous biomass, such as agricultural residues, algal biomass, forest residues, manures, activated sludge, energy crops, digestate at high temperature (300–900 °C) and under O2-limiting conditions. The book also highlights the several unique properties of biochar such as an efficient, cost-effective, and environmentally-friendly material for diverse contaminants removal. The variability in physicochemical properties (e.g., surface area, micro-porosity, and pH) provides an avenue for biochar to maximize its efficacy to targeted applications. This book interests academics working in the development of green and sustainable technology in agricultural engineering, material science, chemical engineering, and environmental science.